EDUKASI PERHITUNGAN BIAYA PRODUKSI MENGGUNAKAN PENDEKATAN JOB ORDER COSTING PADA KOMUNITAS PENJAHIT GAUN DAN KEBAYA DI RINGINPITU, TULUNGAGUNG - Dianita Meirini; Binti Nur Asiyah; Tashya Novita Puji Rahayu (LPPM Universitas Abdurrab, 2025)
Accuracy in calculating the cost of production is a key factor in determining selling prices, ensuring that locally produced goods can compete with imported products. The most suitable method to apply is job order costing, which is a production cost calculation method based on specific orders. This method is particularly appropriate for companies that manufacture goods according to special requests or customer specifications. Indonesia’s fashion industry continues to grow every year, contributing an export value of up to USD 16.5 billion in 2022. The production of dresses and kebaya, which is generally order-based, also faces challenges in determining production costs, particularly in the calculation of manufacturing expenses. Accurate production cost calculation directly influences selling prices, revenue, and business profits, and on a macro scale also contributes to export value. Therefore, an educational program on production costs using the job order costing approach was conducted for the dress and kebaya tailoring community in Ringinpitu, Tulungagung. Initial findings indicated that the community had not included overhead costs (such as electricity, rent, and machine maintenance) in their calculation of production costs. The educational activities covered an understanding of the basic concepts of job order costing, hands-on practice in cost calculation using order cards, and techniques for determining product selling prices. The results showed a significant improvement in participants understanding after the educational sessions, the increase is approximately 56%. This was evidenced by the paired sample t-test, which demonstrated a difference between the pretest score (mean = 59.00) and the posttest score (mean = 92.00) with a significance level of α = 0.000.